Cross-border bank lending, risk aversion and the financial crisis - Cornelia Düwel; Rainer Frey; Alexander Lipponer (Deutsche Bundesbank, 2011)
This study investigates the determinants of adjustments in the provision of cross-border loans by internationally active banks. For the period from 2002 to 2010, we look at quarterly transaction data (excluding valuation effects) on long-term loans issued by the largest 69 German banking groups to the private sector of 66 countries. We show that the parent bank's lending adjustment is based almost exclusively on supply-side determinants, in particular on bank-specific factors. However, foreign countries' demand and risk characteristics become more relevant when loans are distributed by banks' affiliates located abroad. Focusing on risk measures such as the parent bank's ratio of Tier I capital to risk-weighted assets, we find that rising risk aversion among banks curbed cross-border lending during the financial crisis, especially at a later stage following the collapse of Lehman Brothers. However, we find a threshold at around 11% of the Tier I capital ratio above which an increase in the ratio does not curb lending anymore.
Keywords: G21; F23; F34; 330; cross-border lending; banks; financial crisis; Internationale Kreditvergabe; Internationale Bank; Finanzmarktkrise; Risikoaversion; Welt